دراسة فعالية شرائح البولي إيتيلين في الحد من تأثير الأشعة فوق البنفسجية من نمط UV-B في أصبغة التركيب الضوئي والنقل الإلكتروني الضوئي لدى أوراق نباتات دوار الشمس الفتية Helianthus sp. - عياش عبد الكريم; العوض دانيال; كحيلي رزان (Latakia University Journal -Biological Sciences Series, 2017)
جرى تعريض نباتات دوار الشمس الفتية للأشعة فوق البنفسجية من النمط UV-B(295nm) لمدة 3 أيام (ساعتين/ يومياً)، مع أو بدون حجب الأشعة بشرائح البولي إيتيلين (أزرق، وشفاف) بسماكة مقدارها (0.5 مم). تم قياس كمية أصــــــبغة التركيــب الضـــوئي، إذ لوحــــظ تبـــــاين في كمية اليخضـــــور (chl.a)فيها بنســــب ( دون حجب 19.59% ، بولي ايتيلين شفاف 3.40%، بولي ايتيلين أزرق 1.66% )، واليخضور ( (chl.b (22.79 , 25.13 , 7.81 %)، والمحتوى الكلي لليخضور(20.53 , 21.76 , 2.88%)، بينما ارتفعت كمية الأصبغة الكاروتينويدية في العينات المدروسة (17.32 , 19.23 , 24.45%) على التوالي. لوحظ انخفاض في شـــــدة النقل الالكتروني الضوئي (88.04, 78.71 , 58.81%) في العينات النباتية المعرضة للأشـــعة فوق البنفسجية (في اليوم الثالث) على التوالي، وتمت مقارنة جميع النتائج بالشاهد الذي لم يتعرض للأشعة. تشير النتائج إلى التأثير السلبي للأشعة فوق البنفسجية في المحتوى اليخضوري، ومعدلات النقل الالكتروني وبالتالي في التركيب الضوئي و إنتاجية نباتات دوار الشمس. كما تشير من جهة أخرى إلى أهمية الأصبغة الكاروتينويدية في حماية الأصبغة اليخضورية من التأثير السلبي لهذه الأشعة. أظهرت النتائج الـتأثير الإيجابي الواضح لشرائح البولي إيتيلين وخاصة الزرقاء منها في حماية النباتات تجاه هذه الأشعة. Young sun flower plants were exposed to ultraviolet radiation of the type UV-B (295 nm) for 3 days (2 hours per day) with or without excluding the UV-radiations using polyethylene layers (blue and transparent) (0.5 mm thick). The amount of photosynthesis pigments was measured whereby a variation in the chlorophyll contents. Chlorophyll a (chl.a) was noticed at these rates (without covering 19.59%, transparent polyethylene 3.40%, blue polyethylene 1.66%), chlorophyll b (chl.b) at rates (7.81, 25.13, 22.79%) and the total chlorophyll content (2.88, 21.76, 20.53%), while the amount of carotenoid pigments has increased in the studied samples (24.45, 19.23, 17.32%). A decrease in the rate of photosynthetic electron transport has also been noticed (88.04, 78.71, 58.81%) in the plant samples exposed to ultraviolet radiation (on the third day) without UV excluding and with transparent and blue polyethylene successively. All results were compared to the sample which was not exposed to radiation. All results indicate the negative effect of ultraviolet radiation on the chlorophyll content and the rate of photosynthetic electron transport, therefore, on photosynthesis and the productivity of sun flower plants. They also point out the importance of carotenoid pigments in protecting chlorophyll pigments from the negative effects of this radiation. Results showed the clear positive effect of polyethylene layers, specifically the blue one, in protecting plants against this radiation.